Sketching as design thinking - Hoffmann, Alma R. (Routledge, Taylor & Francis Group, 2020)
"This book argues for the importance of sketching as a mode of thinking, and the relevance of sketching in the design process, design education, and design practice. Through a wide range of analysis and discussion, the book looks at the history of sketching as a resource throughout the design process and asks questions such as: where does sketching come from? When did sketching become something different to drawing and how did that happen? What does sketching look like in the present day? Alongside an in-depth case study of students, teachers, and practitioners, this book includes a fascinating range of interviews with designers from a wide variety of backgrounds, including fashion, user experience, and architecture. Sketching as Design Thinking explains how drawing and sketching remain a prominent aspect in our learning and creative process, and provides a rich resource for students of visual art and design"- Resumé vydavatel
Keywords: skici; design; kreslení -- psychologické aspekty; sketches; drawing -- psychological aspects; elektronické knihy; monografie; electronic books; monographs